Biografías, subjetividad y ciencia social. Crítica del enfoque biográfico desde una investigación empírico - Medina, Nuria; Castillo, Susana; Devillard, Marie-José; Touriño, Eva; Pazos, Álvaro (Política y Sociedad, 1995)
Sin resumen